Quantifying the pressure on the teams batting or bowling in the second innings of limited overs cricket matches - Bhattacharjee, D.; Lemmer, H. H. (International Journal of Sports Science & Coaching, 2016)
A team batting second in a limited overs match is under pressure to score the required number of runs for victory in the allotted number of overs without losing all its wickets. The bowling team has to prevent its opponents from reaching the target for victory. The objective of this study is to define methods that can be used to assess the pressure on the two teams` batsmen and bowlers when playing the second innings of a Twenty20 or One-day match, and also to define methods to determine the best partnership and the turning point in such an innings. Methods are also defined to determine the batting and bowling performances of individual players in a specific match. These measures can be quite useful for selectors to assess how the players perform under pressure. ABSTRACT FROM AUTHOR